Pergeseran Tren You Life Only Once ke You Need Only One (Pola Konsumsi Gen Z Perspektif Ekonomi Syariah) - Mutmainnah; Nafis, Abdul Wadud; Cahyani, Wiwik Nur; Mahfiyah; Aliya, Afifatul (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study aims to examine changes in consumption behavior, analyze the influence of a hedonistic lifestyle, and review findings from an Islamic economic perspective. A descriptive quantitative approach was employed, with data collected through an online questionnaire completed by 186 Generation Z respondents in Jember Regency. The t-test results indicate that the YONO trend has a significantly positive impact on awareness of essential consumption, whereas YOLO has a significantly negative impact on awareness of essential consumption. The F-test results show that both YONO and YOLO have a significant positive influence on awareness of essential consumption. These findings suggest a shift from a consumerist culture toward a more prudent and efficient consumption pattern that prioritizes essential needs, aligning with the principles of consumption in Islam among Generation Z in Jember Regency.